2006
DOI: 10.1177/875697280603700505
|View full text |Cite
|
Sign up to set email alerts
|

Projects and Project Managers: The Relationship between Project Managers' Personality, Project Types, and Project Success

Abstract: The fit between project managers' personality and management style and the types of projects they manage is crucial for projects' success. This exploratory interdisciplinary study focuses on the relationships among three aspects: projects' types (profiles), project managers' personality, and projects' success. Based on the person-organization fit theory it was hypothesized that a project with a particular profile needs a manager with fitting personality traits in order to achieve optimal performance and succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 51 publications
3
141
0
8
Order By: Relevance
“…A importância de aspectos relacionados às pessoas envolvidas no projeto também tem sido foco de crescente interesse, salientando-se fatores como a adequação da personalidade do gerente e seu estilo de liderança ao tipo de projeto (DVIR; SADEH; MALACH-PINES, 2006;Prabhakar, 2005;TURNER;. Dvir, Sadeh e Malach-Pines (2006) partiram da teoria da adequação organização-indivíduo e levantaram a hipótese de que um projeto com um perfil particular precisa de um gerente com traços de personalidade que se enquadrem de modo a alcançar o sucesso.…”
Section: Fatores Críticos De Sucesso Em Projetosunclassified
See 1 more Smart Citation
“…A importância de aspectos relacionados às pessoas envolvidas no projeto também tem sido foco de crescente interesse, salientando-se fatores como a adequação da personalidade do gerente e seu estilo de liderança ao tipo de projeto (DVIR; SADEH; MALACH-PINES, 2006;Prabhakar, 2005;TURNER;. Dvir, Sadeh e Malach-Pines (2006) partiram da teoria da adequação organização-indivíduo e levantaram a hipótese de que um projeto com um perfil particular precisa de um gerente com traços de personalidade que se enquadrem de modo a alcançar o sucesso.…”
Section: Fatores Críticos De Sucesso Em Projetosunclassified
“…No entanto, a articulação da literatura de fatores críticos de sucesso (BELOUT; GAUVREAU, 2004;MIRANDOLA, 2007;COOKE-DAVIES, 2002;DINSMORE, 1998;SADEH;MALACH-PINES, 2006;FORTUNE;WHITE, 2006;GRANOT, 1997;JUDGEV;OBIKUNLE, 2001;MANTEL, 1990;PRESCOTT, 1988;SLEVEN, 1987, 1988, PRABHAKAR, 2005RABECHINI JR. et al, 2002;RUUSKA;VARTIAINEN, 2003;TURNER;UMBLE et al, 2003;WESTERVELD, 2003) com a abordagem contingencial ainda é tênue.…”
Section: Conclusãounclassified
“…Greater uncertainty exists as the project manager and team have minimal experience using new technologies (Dvir, Sadeh & Malach-Pines 2006;Tatikonda & Rosenthal 2000). For example, enterprise resource planning projects are often implemented to replace current systems and employ a vast amount of new technologies which work in tandem to create a fully integrated organisational ICT system.…”
Section: Project Typesmentioning
confidence: 99%
“…Researchers have argued that in this view the human aspects of management are ignored. As a result this traditional view with its focus on top-down control, centralized command and communication, and outputs is now seen as ineffective as it may not be an optimal approach and it may even be counterproductive to overall project performance (Thamhain, 1996(Thamhain, , 2004Shenhar, 2001; The Electronic Journal of Information Systems in Developing Countries www.ejisdc.org Dvir et al, 2006). Studies have identified changes in the roles of project leaders to act more as coaches, facilitators, and coordinators than as supervisors and in addition to enhancing efficacy an important task for the leader is to minimize conflicts among team members and build cohesion and identity (Brown and Gioia, 2002).…”
Section: Pinto Et Al's Modelmentioning
confidence: 99%